2016
DOI: 10.2174/1389200216666151103115654
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Supplementation and Exercise in Healthy Humans: A Systematic Review

Abstract: CoQ10 has properties related to bioenergetic and antioxidant activity; thus, it is intimately involved in energy production and in the prevention of peroxidative damage to membrane phospholipids and of free radical-induced oxidation. These properties make it suitable as a dietary supplement to improve cellular bioenergetics and to inhibit certain age-related pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…Thus, in our study, we observed a positive effect of a shortterm supplementation with Ubiquinol on the levels of 8-OHdG in T4 (urine) and T5 (plasma) and plasma peroxides in T4. Other studies have also shown an effect of Coenzyme Q10 on the oxidative damage to DNA and lipids in situation of strenuous exercise [10,11].…”
Section: Tablementioning
confidence: 88%
“…Thus, in our study, we observed a positive effect of a shortterm supplementation with Ubiquinol on the levels of 8-OHdG in T4 (urine) and T5 (plasma) and plasma peroxides in T4. Other studies have also shown an effect of Coenzyme Q10 on the oxidative damage to DNA and lipids in situation of strenuous exercise [10,11].…”
Section: Tablementioning
confidence: 88%
“…CoQ10 could be suitable for a muscle-protective supplementation because it has anti-inflammatory and antioxidant activity and it is intimately involved in energy production [39,40]. However, scarce studies of CoQ10 supplementation investigating its effects during strenuous physical exercise are available in the scientific literature, especially in the field of the inflammatory signaling and hematological parameters and virtually nonexistent when referring to supplementation with the reduced form of this molecule (ubiquinol) [29,39]. Both groups studied were homogeneous in terms of weight, height, blood pressure, and age.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ubiquinol prevented the decrease in RBC, hemoglobin, and hematocrit after the first physical test, a fact that would increase oxygen delivering to tissues, especially muscles. During exercise, oxidative stress induces deleterious structural and functional changes in RBC, however, ubiquinol prevents those changes in erythrocytes, due to its antioxidant properties [29], avoiding the impairment in hematological changes such as decreases in Hb and RBC caused by strenuous exercise [11]. In addition, ubiquinol supplementation also increases NO output [32], a fact that is beneficial during physical activity, featuring a vasodilator action that helps both exercise performance and nutrient supply in muscle recovery, as well as improvement in the supply of substrates such as glucose, together facilitate the regulatory role in the immune system [57].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a placebo controlled study with supplementation of 300 mg of ubiquinol for 6 weeks significantly enhanced physical performance, which was measured as the maximum power output in young healthy trained Olympic athletes [48]. A systematic review to analyze the influence and effect of CoQ 10 supplementation on parameters related to exercise in healthy humans revealed that CoQ 10 has the potential to be used as a nutritional supplement to improve exercise capacity; however, the current literature shows a disparity and inconsistency, possibly due to differences in the CoQ 10 formulations used, dosage, timing of the supplement, exercise tests performed and study participants [49]. …”
Section: Discussionmentioning
confidence: 99%